2017
DOI: 10.7895/ijadr.v6i1.238
|View full text |Cite
|
Sign up to set email alerts
|

Exploring perceptions of alcohol use in two Indian states: A qualitative study from Delhi and Haryana, India

Abstract: Aims: To explore perceptions and determinants influencing alcohol consumption, with a view to inform development of suitable policies to control alcohol consumption.Methodology: Focus group discussions (FGDs) (n=24) were conducted in two Indian states among the rural Haryana (n=8 FGDs; 58 participants) and urban Delhi (n=16 FGDs; 113 participants) populations. Purposive sampling was used to recruit the participants, who were from high and low socioeconomic status (SES) groups and in the age group of 18-58 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…Consistent with existing research [ 25 ], we found statistically significant gender differences in the quantity consumed, with Indian females drinking less than males, but not in the expected difference in prevalence of drinking. This is potentially attributed to rapidly changing attitudes towards female alcohol use in India, especially among higher status groups [ 32 ]. Hence, these findings warrant more research exploring alcohol use among higher status groups and those with high levels of education, in India.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with existing research [ 25 ], we found statistically significant gender differences in the quantity consumed, with Indian females drinking less than males, but not in the expected difference in prevalence of drinking. This is potentially attributed to rapidly changing attitudes towards female alcohol use in India, especially among higher status groups [ 32 ]. Hence, these findings warrant more research exploring alcohol use among higher status groups and those with high levels of education, in India.…”
Section: Discussionmentioning
confidence: 99%
“…The legal drinking age in India ranges from 18 to 25 years, with sales banned to the whole population in certain states [ 31 ]. However, with urbanization and industrialization, economic transition, exposure through extensive alcohol marketing, increased availability, and relaxation of overseas trade rules; alcohol use is increasing in India [ 31 , 32 ]. Hence, both traditions and social change influence drinking culture in modern India [ 28 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study suggests that females consume less alcohol, and that those who consume it use home-brewed or country liquor (Kumar et al, 2018). Furthermore, another study has shown that drinking among women was earlier a taboo, but now women are often drinking at social gatherings (Arora et al, 2017). Several other behavioral and metabolic risk factors may cause chronic diseases among women.…”
Section: Discussionmentioning
confidence: 99%